Integrative Analysis of HTNV Glycoprotein Derived MHC II Epitopes by In Silico Prediction and Experimental Validation - Sun, Hao; Lu, Zhenhua; Xuan, Guoyun; Liu, Ning; Wang, Tianhu; Liu, Yang; Lan, Mingfu; Xu, Jiahao; Feng, Yuancai; Xu, Shuang; Lu, Yuchen; Sun, Baozeng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Hantaan virus (HTNV), the causative pathogen of hemorrhagic fever with renal syndrome (HFRS), is a negative RNA virus belonging to the Orthohantaviridae family. HTNV envelope glycoprotein (GP) encoded by the genomic medium segment is immunogenic and is therefore a promising vaccine candidate. Major histocompatibility complex class I (MHC-I) epitopes derived from HTNV have been extensively studied, but little is known of MHC-II epitopes. In silico predictions based on 4 databases indicated that the full-length HTNV GP has 1121 15-mer epitopes, of which 289 had a high score for binding to the human and murine MHC-II superfamily. We found that epitope ILTVLKFIANIFHTS could potentially bind most MHC-II molecules covering human and murine haplotypes. Dominant epitopes were validated by enzyme-linked immunospot assay of splenocytes from immunized mice; 6 of 10 epitopes supported the predictions including TATYSIVGPANAKVP, TKTLVIGQCIYTITS, FSLLPGVAHSIAVEL, CETYKELKAHGVSCP, CGLYLDRLKPVGSAY, and NLGENPCKIGLQTSS. Conservation analysis of dominant epitopes revealed host–virus interactions without geographic stratification, thus meeting the requirements of candidate vaccines for large-population prophylaxis. These findings provide insight into hantavirus antigenicity and suggest that vaccines targeting MHC-II can provide immune protection to complement symptomatic therapies for the treatment of HFRS.